2014
DOI: 10.1080/02681102.2013.874318
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Quality and Quantity of Tertiary-Level Information Systems Students: A Graduate Development Framework

Abstract: This article forms part of research-in-progress aimed towards creating a comprehensive graduate development framework that will assist Information Systems (IS) departments in increasing the quality and quantity of their enrolments and graduates.In this article we present the IS Graduate Development Framework (ISGDF). This framework combines measurable, tested variables from four IS education related fields of study into a single framework for measuring the graduate development potential of IS institutions, cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…For this purpose, they analyse online databases and websites of existing programmes and universities around the world. In another study, [3] use Information Systems (IS) education concepts and course structures to develop a framework to counteract the IS skills deficiency in South Africa.…”
Section: Related Workmentioning
confidence: 99%
“…For this purpose, they analyse online databases and websites of existing programmes and universities around the world. In another study, [3] use Information Systems (IS) education concepts and course structures to develop a framework to counteract the IS skills deficiency in South Africa.…”
Section: Related Workmentioning
confidence: 99%
“…There have been several studies in South Africa which aimed to investigate the supply and demand of ICT jobs (Alexander et al, 2014; Breytenbach and De Villiers, 2012; Breytenbach and De Villiers, 2015; Merkofer and Murphy, 2009). All of these studies found that there was a shortage of skills in ICT.…”
Section: Ict Skills Gap In South Africamentioning
confidence: 99%
“…This in turn leads to increased demand for ICT skills with a more price-elastic supply, which is translated as higher wages. In another research, Breytenbach and De Villiers (2015) investigated concerns and key concepts influencing IS graduate quality and quantity in South Africa. The authors also developed a framework that will assist IS departments in increasing the quality and quantity of their enrolments and graduates.…”
Section: Ict Skills Gap In South Africamentioning
confidence: 99%